A vontade da verdade, a informação e o arquivo - (:unkn) unknown (Universidade Federal do Rio de Janeiro / Instituto Brasileiro de Informação em Ciência e Tecnologia, 2012)
This work investigates a possible relationship between a will of truth, the information and the archives observing its development through action to document in its genesis. Presents a discussion based on the philosophy of Michel Foucault on the question of truth and meaning of the Archive. Locates the problem with the current discussion on the opening of the archives of the period of the Brazilian Military Regime, where there is a conflict between truth and will of the documentary sources in the custody of the Archives. Includes discussion on the different perspectives on the relationship between truth and use the information to the Information Science, Archival Science and History, disciplines commonly linked to deals with the documentary sources, presenting differences in such areas of knowledge on the validation of information. This dissertation finally concludes that recent studies on a Philosophy of Information based on documentary practices, started by Bernd Frohmann in Information Science, open a possible path of research to enrich the debate on the subject
Keywords: Truth; Information; Action to document; Document; Archive; Informação; Arquivo; Brazilian Military Regime; Documentação; Documento; Philosophy of Information; Filosofia da informação; Ciência da informação